Electron Paramagnetic Resonance Spectrometry and Imaging in Melanomas: Comparison between Pigmented and Nonpigmented Human Malignant Melanomas - Quentin Godechal; Ghanem E. Ghanem; Martin G. Cook; Bernard Gallez (Molecular Imaging)
It has been known for a long time that the melanin pigments present in normal skin, hair, and most of malignant melanomas can be detected by electron paramagnetic resonance (EPR) spectrometry. In this study, we used EPR imaging as a tool to map the concentration of melanin inside ex vivo human pigmented and nonpigmented melanomas and correlated this cartography with anatomopathology. We obtained accurate mappings of the melanin inside pigmented human melanoma samples. The signal intensity observed on the EPR images correlated with the concentration of melanin within the tumors, visible on the histologic sections. In contrast, no EPR signal coming from melanin was observed from nonpigmented melanomas, therefore demonstrating the absence of EPR-detectable pigments inside these particular cases of skin cancer and the importance of pigmentation for further EPR imaging studies on melanoma.